Botley 2.0, the coding robot [library of things]. (Learning Resources, inc., 2018)
"Meet Botley 2.0 The Coding Robot, our smartest coding robot yet! The next generation of our Toy of the Year winner Botley the Coding Robot, Botley 2.0 helps kids as young as 5 learn to code through 100% screen-free play. Botley 2.0 knows multiple ways to code right out of the box--code by color, make Botley move in six directions, and even put on a light show! Discover Botley 2.0's 16 fun interactions--transform Botley into a train, police car, ghost, and more! You can even test your memory with the lights and sounds of a game of Botley Says! Your little coders can build coding sequences of up to 150 steps, and go on adventures with a built-in sensor that lights up Botley 2.0 in the dark! With the help of Botley's 78-piece activity set, kids will be solving their first coding and STEM challenges in just minutes! "--